Eosinophilic esophagitis with and without airway involvement in children – A comparative analysis. (December 2020) - Bora, Varun; Olive, Anthony; Chiou, Eric; Raj, Priya; Mehta, Deepak
Abstract: Background: Eosinophilic esophagitis (EoE) is an allergic disease characterized by marked eosinophilic infiltration and inflammation of the esophagus eventually leading to esophageal dysfunction. This condition at times may involve the airway leading to breathing difficulties. Objective: To compare the course of EoE in patients with or without airway involvement. Methods: A retrospective chart review was done on patients with a diagnosis of Eosinophilic Esophagitis and that were managed in our Aerodigestive clinic from 2012 to 2018. A total of 121 EoE patients were included in the study. Each patient's disease course was examined for pertinent information including – but not limited to – age at presentation, allergies, endoscopic and pathology results, treatments prescribed, and time to resolution. The data was analyzed for any differences between the airway and non-airway groups for each of these variables. Results: The variables that were analyzed showed no significant difference between patients suffering from EoE with (n = 19) and without (n = 102) airway involvement. However, patients with airway disease trended towards being younger in age at presentation as compared to those without airway symptoms (6.68 years vs. 9.69 years, p = 0.69 ). Analysis of endoscopic and pathology findings revealed no difference. Similarly, no differences were found between the prescribed treatments. Kaplan-Meier estimates of time to disease remission indicated that 50% of patients had resolution at one year, regardless of airway involvement (p = 0.31). Conclusions: Our findings indicate that the disease course of patients with EoE does not vary depending on the presence of airway symptoms. Thus, patients with airway symptoms should not be diagnosed or treated any different than those without airway symptoms.